Designing Pricing Strategy for Operational and Technological Transformation - Kumar, Vineet; Sun, Yacheng (Management Science, 2020)
We examine how operational or technological transformation impacts consumer value, as well as the effectiveness of a firm’s pricing strategies. We develop a model of multidimensional screening featuring forward-looking consumers who make short-run consumption and long-run purchase decisions. Using a detailed panel of consumer data from a rental-by-mail firm, we estimate consumer utility for current consumption, obtaining heterogeneous preferences for bunching and smoothing consumption. Using counterfactual analysis, we evaluate the impact of improving service time. We find that the firm with improved service time might create more value for all consumers, but its profits and even revenues could diminish because value extraction becomes more difficult. We find a novel mechanism that causes this effect, which is driven by increased consumer heterogeneity in the valuation for each product and reduced differentiation across products. This result persists even when the firm can reoptimize its price levels based on the service time. We find that a change in the pricing strategy might be required for the firm to obtain higher revenue with improved service time. This paper was accepted by Matthew Shum, marketing.